Gender Identity and Sexual Function in 46,XX Patients with Congenital Adrenal Hyperplasia Raised as Males. - Apóstolos, Robson A. C.; Canguçu-Campinho, Ana Karina; Lago, Renata; Costa, Ana Carolina S.; Oliveira, Luciana M. B.; Toralles, Maria Betania; Barroso, Ubirajara; Barroso, Ubirajara Jr (Archives of Sexual Behavior, 2018)
In individuals with congenital adrenal hyperplasia (CAH) and 46,XX karyotype, androgens produced by the adrenal glands during the intrauterine development promote virilization of the genitals, which may even result in the development of a well-formed penis. Some of these children with late diagnosis are registered as males after birth. After obtaining approval from the internal review board, we evaluated gender identity and sexual function in four 46,XX severely virilized patients with CAH, who were originally registered and raised as males, assisted in our Disorders of Sexual Development Clinic. The evaluation consisted of questionnaires to assess gender identity and sexual activity and interview with the multidisciplinary team that provides care for these patients. The patients underwent surgery to remove uterus, ovaries, and remaining vaginal structures, in addition to implantation of testicular prosthesis and correction of hypospadias, when necessary. All four patients have developed a clear male gender identity, and when evaluated for sexual activity, they have reported having erections, libido, orgasms, and sexual attraction to women only. Two of these 4 patients had satisfactory sexual intercourses when assessed using the International Index of Erectile Function questionnaire. The other two patients who never had sexual intercourse reported not having a partner for sexual activity; one is 18 years old, and the other is 14 years old. This study showed that this group of 46,XX severely virilized patients with CAH, registered and raised as males, adapted well to the assigned male gender, with satisfactory sexual function in patients who had sexual intercourse.